2017
DOI: 10.1002/ecs2.1943
|View full text |Cite
|
Sign up to set email alerts
|

Non‐linear thresholds characterize the relationship between reef fishes and mangrove habitat

Abstract: . 2017. Non-linear thresholds characterize the relationship between reef fishes and mangrove habitat. Ecosphere 8(9):e01943. 10. 1002/ecs2.1943 Abstract. A significant obstacle to evaluating the importance of mangrove habitat to coral reef fishes has been the difficulty of disentangling its effects from other subtidal/nearshore habitats or human population pressures. Florida's seascape, unlike most others, has been extensively surveyed and mapped, and there are reliable estimates of human population density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…Nonetheless, fine-scale BPI and two other fine-scale metrics of seafloor surface complexity-curvature and rugosity-were dropped entirely from both MaxEnt models. These results indicate that the distributions of sub-adult L. griseus and H. sciurus across the seascape are primarily driven by broad-scale habitat features and geographic location, a finding that is consistent with previous research on predatory reef fishes and which may be related to the high vagility and large home range sizes of these species (1-5 km) [96][97][98][99]. However, previous work in the Caribbean revealed that seafloor morphology and geographic location interact to drive the distributional patterns of herbivores, in addition to invertivores and piscivores, suggesting that this trend is likely common across coastal reef fish communities rather than being restricted to mobile predators [68].…”
Section: Variable Importancesupporting
confidence: 90%
“…Nonetheless, fine-scale BPI and two other fine-scale metrics of seafloor surface complexity-curvature and rugosity-were dropped entirely from both MaxEnt models. These results indicate that the distributions of sub-adult L. griseus and H. sciurus across the seascape are primarily driven by broad-scale habitat features and geographic location, a finding that is consistent with previous research on predatory reef fishes and which may be related to the high vagility and large home range sizes of these species (1-5 km) [96][97][98][99]. However, previous work in the Caribbean revealed that seafloor morphology and geographic location interact to drive the distributional patterns of herbivores, in addition to invertivores and piscivores, suggesting that this trend is likely common across coastal reef fish communities rather than being restricted to mobile predators [68].…”
Section: Variable Importancesupporting
confidence: 90%
“…Few studies have explicitly tested abrupt changes in densities and biomasses of fish nursery species with distance away from nursery areas (but see Nagelkerken et al , Shideler et al ). Furthermore, threshold distances have rarely been estimated.…”
Section: Discussionmentioning
confidence: 99%
“…For example, fish nursery species in the Caribbean were found to rapidly decline at a distance of 4 km from nurseries and most nursery species were absent at locations 14 km away from nurseries (Nagelkerken et al ). Additionally, Shideler et al () found that species richness on Caribbean coral reefs declined with decreasing mangrove extent at scales < 20 km 2 . A larger proportion of Caribbean juvenile reef fishes utilise mangroves compared to seagrass as nursery habitat, while seagrass beds are utilised by a larger number of species as nursery habitat by Indo‐Pacific reef fishes, the major driver of this phenomena being the differences in tidal amplitudes (Igulu et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, there is often an expectation that increasing habitat availability (e.g., abundance and connectivity of habitat suitable for consumer occupancy) will lead to greater population size or secondary production (Palmer, Ambrose, & Poff, 1997). While this assumption usually underpins habitat restoration efforts, it has been complicated by numerous studies documenting nonlinear (unimodal and threshold) effects of habitat availability on consumer performance (Allouche, Kalyuzhny, Moreno-Rueda, Pizarro, & Kadmon, 2012;Shideler, Araujo, Walker, Blondeau, & Serafy, 2017;Venier & Fahrig, 1996).…”
Section: Introductionmentioning
confidence: 99%